Do Employee Stock Ownership Plans Affect the Quest for Firm Profitability? Evidence from Tanzania - Beny Mwenda; Magwana Ibrahim Ngollo (Universitas Airlangga, 2023)
Objective: The purpose of this research is to examine the impact of Employee Stock Ownership Plans (ESOP) on firms' profitability of Tanzanian publicly listed firms. Design/Methods/Approach: The research utilized a longitudinal research design by employing secondary data from firms listed in the Dar es Salaam Stock Exchange (DSE). The random effect model with two estimations was utilized to analyze data. Findings: Results suggest that ESOP has a positive and significant effect on the firm's quest for profitability. Originality: The originality or uniqueness of this study lies in providing further understanding from a different economic and cultural perspective and enhancing the results of academic studies in this area. Practical/Policy implication: For business owners, the results of this study can be used as a root from which they can have a reason to grow their own ESOP and increase their wealth. For policymakers, it is a base for policy formulation that will enhance the profitable tax base.